Prediction of factors affecting amlodipine induced pedal edema and its classification - Chopra A.; Dimri A.; Pradhan T. (My University, 2025)
Calcium channel blockers (CCB) disrupt the movement of calcium and prevent it from entering cells of the blood vessel walls. They are used to widen blood vessel resulting in lower blood pressure. Amlodipine is one such calcium channel blocker that dilates the blood vessel and improves blood flow. It is used to treat angina, high blood pressure and hypertension. Amlodipine is quite effective in treating aforementioned conditions but it has been found to induce pedal edema in patients. In this paper, we have evaluated the causative factors for Amlodipine induced pedal edema and also performed a classification of patients based on the side effects of Amlodipine. © 2017 IEEE.